Studi Kelayakan Bisnis dari Aspek Keuangan - Diva Ananda; Dyah Asti Ningrum; Risda Adila (Trending: Jurnal Manajemen dan Ekonomi, 2025)
The purpose of this research is to determine the importance of financial elements when starting a business. Literature research or literature review uses written sources such as scientific journals, reference books, encyclopedias, and other reliable sources, both in written and digital form, that are relevant and pertinent to the research subject. The results and discussion on the importance of financial elements in business feasibility studies help entrepreneurs make better decisions and reduce financial risks.